Welcome to our community

Be a part of something great, join today!

[SOLVED] 2.1.1 }Solve the given differential equation

karush

Well-known member
Jan 31, 2012
2,928
$\textsf{Given}$
$$\displaystyle y^\prime + 3y = x + e^{-2x}$$
$\textit{Solve the given differential equation}$
\begin{align*}\displaystyle
&\textit{book answer is}\\
y&=\color{red}{\displaystyle ce^{-3x}+\frac{x}{3}-\frac{1}{9}+e^{-2x}}
\end{align*}
no sure how $ce^{-3x}$ was derived?

$\tiny{2.1.1}$
 

MarkFL

Administrator
Staff member
Feb 24, 2012
13,775
Typically, when given a linear first order ODE of the form:

\(\displaystyle \d{y}{x}+f(x)y=g(x)\)

You want to look for an integrating factor in the form:

\(\displaystyle \mu(x)=\exp\left(\int f(x)\,dx\right)\)

What would your integrating factor be for this problem?
 

karush

Well-known member
Jan 31, 2012
2,928
Typically, when given a linear first order ODE of the form:

\(\displaystyle \d{y}{x}+f(x)y=g(x)\)

You want to look for an integrating factor in the form:

\(\displaystyle \mu(x)=\exp\left(\int f(x)\,dx\right)\)

What would your integrating factor be for this problem?
$\d{y}{x}+Py=Q$


not real sure but if P=3 then
$$I=e^{\int 3 \, dx}$$
 

MarkFL

Administrator
Staff member
Feb 24, 2012
13,775
$\d{y}{x}+Py=Q$


not real sure but if P=3 then
$$I=e^{\int 3 \, dx}$$
Simplify it by evaluating the integral (without the constant of integration). What do you get?
 

MarkFL

Administrator
Staff member
Feb 24, 2012
13,775
With the integrating factor defined as:

\(\displaystyle \mu(x)=\exp\left(\int f(x)\,dx\right)\)

It then follows that:

\(\displaystyle \mu'(x)=\exp\left(\int f(x)\,dx\right)f(x)\)

And thus, when you multiply the general ODE I posted by this factor, you obtain:

\(\displaystyle \mu(x)\d{y}{x}+\mu'(x)y=\mu(x)g(x)\)

We should observe now that the LHS can be rewritten as the derivative of a product:

\(\displaystyle \frac{d}{dx}\left(\mu(x)y(x)\right)=\mu(x)g(x)\)

And now it is possible to solve for $y(x)$ after integrating. I will await your attempt to apply this method to the given problem. :)
 

karush

Well-known member
Jan 31, 2012
2,928
With the integrating factor defined as:

\(\displaystyle \mu(x)=\exp\left(\int f(x)\,dx\right)\)

It then follows that:

\(\displaystyle \mu'(x)=\exp\left(\int f(x)\,dx\right)f(x)\)

And thus, when you multiply the general ODE I posted by this factor, you obtain:

\(\displaystyle \mu(x)\d{y}{x}+\mu'(x)y=\mu(x)g(x)\)

We should observe now that the LHS can be rewritten as the derivative of a product:

\(\displaystyle \frac{d}{dx}\left(\mu(x)y(x)\right)=\mu(x)g(x)\)

And now it is possible to solve for $y(x)$ after integrating. I will await your attempt to apply this method to the given problem. :)
i presume you imply taking the integral of both sides first
$$\frac{d}{dx}\left(\mu(x)y(x)\right)=\mu(x)g(x)$$
$$\mu(x)y(x)=\int\mu(x)g(x) \, dx $$
 

MarkFL

Administrator
Staff member
Feb 24, 2012
13,775
i presume you imply taking the integral of both sides first
$$\frac{d}{dx}\left(\mu(x)y(x)\right)=\mu(x)g(x)$$
$$\mu(x)y(x)=\int\mu(x)g(x) \, dx $$
Yes, that's what you have after integrating. And then you may state:

\(\displaystyle y(x)=\frac{1}{\mu(x)}\left(\int \mu(x)g(x)\,dx\right)\)

Can you apply this technique to the given problem?
 

karush

Well-known member
Jan 31, 2012
2,928
Yes, that's what you have after integrating. And then you may state:

\(\displaystyle y(x)=\frac{1}{\mu(x)}\left(\int \mu(x)g(x)\,dx\right)\)

Can you apply this technique to the given problem?
ok I think I'm lost on $\mu(x)g(x)$
\begin{align}\displaystyle
\frac{d}{dx}\left(\mu(x)y(x)\right)&=\mu(x)g(x)\\
y^\prime &= x + e^{-2x}-3y\\
y+3&=\frac{1}{x}+e^{-2x}\\
book \, answer&\\
y&=\color{red}{\displaystyle ce^{-3x}+\frac{x}{3}-\frac{1}{9}+e^{-2x}}
\end{align}
 

MarkFL

Administrator
Staff member
Feb 24, 2012
13,775
We have the integrating factor:

\(\displaystyle \mu(x)=e^{3x}\)

Multiplying the given ODE by this factor we obtain:

\(\displaystyle e^{3x}y'+3e^{3x}y=xe^{3x}+e^{x}\)

Rewriting the LHS, we now have:

\(\displaystyle \frac{d}{dx}\left(e^{3x}y\right)=xe^{3x}+e^{x}\)

Integrating w.r.t $x$, we get:

\(\displaystyle e^{3x}y=\frac{1}{9}e^{3x}(3x-1)+e^x+c_1\)

Hence:

\(\displaystyle y(x)=\frac{1}{9}(3x-1)+e^{-2x}+c_1e^{-3x}\)

This is equivalent to the answer given by your book. :)

When you study 2nd (and higher) order linear ODE's, you will be shown other methods to solve problems like this.
 

karush

Well-known member
Jan 31, 2012
2,928
wow, thanks for the awesome:cool: help
I don't start a class in this for 10 weeks yet
but just want to get a head start on it.

this is the best place to come for that.
 

DrWahoo

Active member
Nov 7, 2017
59
Using an integrating factor helps make the differential equations "Exact". Wonderful way to solve simple and some decently complex ode's if you can integrate the integrating factor. Can you check that once you multiply by the integrating factor that you do indeed have an exact ode?